Il caso dell’aborto: una buccia di banana per la SCOTUS? (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. La questione dell’aborto e la perdita di credibilità della Corte Suprema statunitense - 2. Una tempesta perfetta? - 3. La partita della fiducia.The case of abortion: a slippery slope for SCOTUS?ABSTRACT: The case of the right of abortion in the United States is going to represent much more than a mere legal question. The upcoming decision of the Supreme Court of the United States (SCOTUS) on the matter involves its own credibility as a third party institution in a check and balance system where the SCOTUS is increasingly perceived as a political player. In this paper the A. tries to explore why it is so.